PENDEKEATAN KOMUNIKATIF DALAM PENINGKATAN KETERAMPILAN BERBICARA BAHASA INGGRIS DILIHAT DARI MOTIVASI BELAJAR SISWA - putri, anggun kirana (KALAM CENDEKIA PGSD KEBUMEN, 2014)
Communicative Approach in English Speaking Skills in Improvement toward Student Motivation. The purpose of this study was (1) to determine the ratio between the effect of the communicative approach to expository approach in improving English speaking skills, (2) to know English speaking skills toward learning motivation, (3) to determine whether the students communicative approach motivated high learning speaking skills have improved at least better than the other fourth grade students on Alian Kebumen in 2011/2012. This research is a quantitative study using an experimental method with 2 x 2 factorial design and analysis techniques Varian Two Paths (Anava Two Way). The research can be conclude that there is a significant effect of the use of learning approaches and the level of student motivation toward improved English speaking skills, namely the existence of differences in conversational skills in students with low and high motivation, and use the communicative approach and expository. Keywords: Communicative Approach, Speaking Skills, English, Motivation